Length Related Diurnal Vertical Migration of Cod (Gadus morhua L.), Haddock (Melanogrammus aeglefinus L.) and Redfish (Sebastes spp.) in the Barents Sea - Einarsson, Haraldur Arnar (The University of Bergen, 2001)
Vertical fish migrations can increase variability in bottom survey data, especially if unknown diurnal length-frequency distribution is different between layers. Surveys, using echo sounder technique to estimate demersal fish found pelagic, can be seriously biased when using nearby bottom station to estimate the length distribution of pelagic fish. Knowledge about different length-frequency distribution between layers is very important for accurate stock assessments calculations. Three fish species; cod, haddock and redfish were explored from database (1993-1998), collected on demersal fish surveys (January - March) in the Barents Sea. For each species pairs were created of a pelagic station with selected bottom stations, and the length distributions compared between pairs in four categories. The stations were selected according to time of day, depth, distance and day intervals. There was a clear difference in length distributions for all of these three fish species, were the small fish was near the bottom during the light hours, and in the dark hours the small fish moved to pelagic layers. The larger cod and haddock seemed to do the opposite. It is possible to estimate length distribution in the pelagic by using estimators from the distribution in nearby bottom station. The difference between observed and estimated pelagic length distributions was small during the light hours, but larger in the night. Year classes variation between surveys can make the estimators inaccurate. To increase understanding on vertical movement of fish and improve the estimators it is necessary to observe stomach content of the fish and to measure the light were the fish is caught.